Evaluation of a research awareness training programme to support research involvement of older people with dementia and their care partners - Miah, Jahanara (Health Expect, 2020)
BACKGROUND: Best‐practice guidelines recommend that appropriate support be provided to public contributors to facilitate their involvement in research. One form of support is research awareness training. Older people with dementia and care partners were involved in four Research User Groups (RUGs) in the UK, France, Cyprus and Greece. We delivered research awareness training (RAT) to the RUGs. The aim of this study was to evaluate the acceptability and perceived outcomes of the training from the perspective of RUG members. METHODS: At the end of each research training session, participants completed the Training Acceptability Rating Scale‐section 2, which records the respondent's impressions of the training process and the outcomes of training. Participants were also invited to take part in semi‐structured interviews at the end of the programme. RESULTS: Thirty‐four RUG members completed the TARS‐section 2 with 23 completing semi‐structured interviews. Over two‐thirds (67%) of participants rated their overall satisfaction with the RAT ‘a great deal’. Qualitative responses indicated that participants found group work to be beneficial for learning, the structure of training activities and topics covered appropriate. The type and format of the training materials were viewed as helpful, and they valued the new knowledge gained. CONCLUSIONS: The training contents were applicable, useful and relevant to the participants’ role within the research. We highlight the importance of facilitating participation by (a) fostering awareness of relevant research issues and (b) tailoring delivery of training according to the needs of the participants.